Automated Electrostatic Discharge Self-Audit System in Semiconductor Industry - Mad Kaidi, Hazilah; Ampanatham, Puvanieshvaran; Sarip, Shamsul (Journal of Advanced Research in Applied Mechanics, 2020)
Electrostatic Discharge (ESD) is a well-known control process in semiconductor industries, military, medical industry, aerospace industry, oil and gas industry and so on. ESD means the collision between two elements with influence of humidity will create static charges. The static charge will be measured in voltage/inch and then compared with the sensitivity of the Electrostatic Discharge Sensitive (ESDS) items to avoid electronics malfunctions and latent damage to the items. Human Body Model (HBM) tests are done periodically based on the semiconductor industry and customer requirements. The new revision recommends the HBM test done on daily basis for the high control. Common control for HBM involve the footwear test and wrist strap test which done manually. The tighten control for daily test is not possible for manual method of testing, so the idea of converting to automatic testing system are designed and implemented. This design will able to do ESD HBM test daily before entering production floor and the same time adding value as monitoring system as well. The HBM Model test will emphasis hundred percent accuracy of employees testing their ESD attires and also improve the common manual system to an automated system. Implementation of this system will ensure product quality and also minimize the risk of ESD events occurring in semiconductor industry.